Super-capacitor energy storage system to recuperate regenerative braking energy in elevator operation of high buildings - An Thi Hoai Thu Anh; Luong Huynh Duc (Institute of Advanced Engineering and Science, 2022)
In operating phases of elevators, accelerating, braking modes occur frequently, so braking energy recuperation of elevators has contributed considerably to decrease the total electric energy consumption for operating elevators in multi-floor buildings. In this paper, the supercapacitor energy storage system is used to recover regenerative braking energy of elevators when they operate down full-load and up no-load, reducing fluctuation of voltage on DC bus as well. Therefore, super-capacitor energy storage system (SCESS) will be parallel with line utility to recuperate regenerative braking energy in braking phase and support energy for acceleration phase. The surplus energy will be stored in the supercapacitors thanks to a DC-DC converter capable of exchanging energy bidirectionally in buck/boost modes, and designing control strategy including two control loops. Inner loop-current loop: controlling charge/discharge process of supercapacitors by current iL complying with operation characteristic of elevator; Outer loop-voltage loop: managing UDC-link at a fixed value. Simulation results with elevator system of the ten-floor building, Hanoi, Vietnam installed SCESS have been verified on MATLAB Simulink, SimPowerSystem with saving energy level about 30%.